Effect of Isomer Composition of Hydroxy Terminated Polybutadiene (HTPB) in Low Shear Flow Behavior (Efek dari Komposisi Isomer dari Hydroxy Terminated Polybutadiene (HTPB) terhadap Sifat Alir dalam Geseran Rendah) - Restasari, Afni; Abdillah, Luthfia Hajar; Ardianingsih, Retno Ardianingsih; Budi , Rika Suwana (Indonesian Journal of Aerospace, 2020)
HTPB is the ultimate component of matrix builder for high-filled composite materials. Flow behavior of HTPB in low shear is crucial in casting the composite. Considering the characteristics of hydrocarbon, this work aims to investigate the effect of microstructure composition of HTPB on its flow behavior. In this work, HTPB with different composition of 1,4-cis, 1,2-vinyl and 1,4-trans microstructures were used. Fourier-Transform Infra-Red spectroscopy (FT-IR) was used to determine the composition. It was calculated as a ratio of peak area of 710, 910 and 970 cm-1 forÂ 1,4-cis,Â 1,2-vinyl, 1,4-trans isomers respectively. Viscosity was measured using a rotational viscometer at various low shear rates. It is found that HTPB with high 1,2-vinyl/1,4-trans isomersÂ shows shear thickening behaviour, distinguished significantly from Newtonian flow of the others. It is suggested that mechanism of shear thickening involves a certain configuration of 1,2-vinyl and 1,4-trans isomersÂ that builds different degrees of flow resistance from one to other shear layers. The configuration and flow resistance changes among layers as shear increases.